INCREASING PRODUCTIVITY OF FISH FARMERS THROUGH FISH HEALTH AND ENVIRONMENTAL MANAGEMENT TRAINING IN GENTENG DISTRICT, BANYUWANGI - Hapsari Kenconojati; Mohammad Faizal Ulkhaq; Suciyono; Dewi Ambarwati; Sadida Anindya Bahtiar; Eko Wahyudi; Shovia Finny Anggraeni; Leni Mei Ristin (Jurnal Layanan Masyarakat, 2023)
Disease is one of the main problems that have a major impact on aquaculture activities. Diseases in fish generally occur due to an imbalance of interactions between fish, pathogens, and the culture environment. Poor environmental quality can increase stress on fish and increase the pathogenicity of pathogens. In aquaculture activities, it is important to prevent disease in fish to avoid large economic losses. Based on the result of the initial survey, it was found that the problems faced by fish farmers in the Genteng area were the lack of knowledge in identifying the early syndrome of fish disease and the weakness in monitoring the quality of water for cultivation. This program aimed to provide the fish farmer with an introduction to disease kinds, training in environmental health management, and mentoring activities for aquaculture activities so that fish diseases can be prevented as early as possible. This programs were carried out on August 18, 2022, which was attended by 20 fish farmers in the Genteng area and continued with regular assistance for one month. Based on the result, there was an increase in understanding of the identification of parasites in fish, microscope utilization, and water quality test. In general, this programs received a positive response and enthusiasm from training participant, which was accompanied by an increase in participants’ knowledge about how to identify fish disease and water quality test.